First Japanese case of atypical progeroid syndrome/atypical Werner syndrome with heterozygous LMNA mutation. Issue 12 (20th October 2014) - Motegi, Sei‐ichiro; Yokoyama, Yoko; Uchiyama, Akihiko; Ogino, Sachiko; Takeuchi, Yuko; Yamada, Kazuya; Hattori, Tomoyasu; Hashizume, Hiroaki; Ishikawa, Yuichi; Goto, Makoto; Ishikawa, Osamu
Abstract Atypical progeroid syndrome (APS), including atypical Werner syndrome (AWS), is a progeroid syndrome involving heterozygous mutations in the LMNA gene encoding the nuclear protein lamin A/C. We report the first Japanese case of APS/AWS with a LMNA mutation (p.D300N). A 53‐year‐old Japanese man had a history of recurrent severe cardiovascular diseases as well as brain infarction and hemorrhages. Although our APS/AWS patient had overlapping features with Werner syndrome (WS), such as high‐pitched voice, scleroderma, lipoatrophy and atherosclerosis, several cardinal features of WS, including short stature, premature graying/alopecia, cataract, bird‐like face, flat feet, hyperkeratosis on the soles and diabetes mellitus, were absent. In immunofluorescence staining and electron microscopic analyses of the patient's cultured fibroblasts, abnormal nuclear morphology, an increase in small aggregation of heterochromatin and a decrease in interchromatin granules in nuclei of fibroblasts were observed, suggesting that abnormal nuclear morphology and chromatin disorganization may be associated with the pathogenesis of APS/AWS.